Intermediate care in caring for dementia, the point of view of general practitioners - Dibao-Dina, Clarisse (2022)
Funding Information: This study received a European General Practice Research Network (EGPRN) Grant (www.egprn.org) Issue no: 2019/003. Publisher Copyright: Copyright © 2022 Dibao-Dina, Oger, Foley, Torzsa, Lazic, Kreitmayer Peštiae, Adler, Kareli, Mallen, Heaster, Dumitra, Kurpas, Viegas, Giezendanner, Tkachenko, De Lepeleire, Falanga, Missiou, Jennings and Petrazzuoli.